2011
DOI: 10.1039/c1cc12912k
|View full text |Cite
|
Sign up to set email alerts
|

o-Carborane as an electron-transfer mediator in electrocatalytic reduction

Abstract: Electron transfer behavior of 1,2-diphenyl-o-carborane was investigated by cyclic voltammetry (CV). In the presence of 1,2-dibromo-1,2-diphenylethane, a significant catalytic current was observed. The macroscale electrocatalytic reduction of the dibromide using a catalytic amount (1 mol%) of the carborane mediator afforded the desired trans-stilbene in excellent yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 24 publications
2
46
1
2
Order By: Relevance
“…The catalytic current was observed at ¹1.42 V, and the re-oxidation peak at ¹1.28 V disappeared completely as reported for 1,2-diphenyl-o-carborane, which can mediate the debromination reaction of 1,2-dibromo-1,2-diphenylethane to give stilbene. 6 The foregoing results indicate that the carborane-triphenylamine dyad can effectively work as both anodic and cathodic mediator.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The catalytic current was observed at ¹1.42 V, and the re-oxidation peak at ¹1.28 V disappeared completely as reported for 1,2-diphenyl-o-carborane, which can mediate the debromination reaction of 1,2-dibromo-1,2-diphenylethane to give stilbene. 6 The foregoing results indicate that the carborane-triphenylamine dyad can effectively work as both anodic and cathodic mediator.…”
Section: Resultsmentioning
confidence: 92%
“…The redox couple of carborane moiety of 1 was negatively shifted from that of 1,2-diphenyl-o-carborane. 6 To provide a more effective understanding for the optical and electrochemical properties, density functional theory (DFT) calculations for 1 and its component molecules were conducted at B3LYP/6-311G+(2d,p)//B3LYP/6-31G(d) level of theory (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the many closo-and nido-carboranes, carborane-based radical anions featuring a 2n+3 electron count are somewhat rare. [8][9][10][11][12][13] In a more recent report on the photophysics of ortho-carboranes with donating arylcarbazolyl substituents it was suggested that the species in their excited states consist of carbazolyl radical cations and radical cluster anions. This assumption was based on absorption spectroscopy where a transient band at 415 nm with a similar spectral profile as the corresponding radical anion was observed 13 (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 4, their reduction gives rise to two quasireversible closely spaced systems around -1.40 V which can be clearly evidenced on the backward scans of the corresponding time semi-derivative curves (Figure 4b). These are ascribed to the formation of radical anion and dianion species of carborane, [56,57] respectively. Studies with analogous diaryl-substituted ortho-carborane systems have suggested that the electronic charge was located within the carborane cage.…”
mentioning
confidence: 99%